Umbrella review of musculoskeletal injury burden in dancers: implication for practice and research - Anand Prakash, A., K, M.; Akilesh, V. (The Physician and Sportsmedicine, 2024)
Background Dancers are susceptible to injury. Nevertheless, injury epidemiology research in dancers is inconsistent. Furthermore, ballet dancing has dominated the huge body of reviews analyzing the epidemiology of musculoskeletal injuries in a variety of artistic dance forms, making it challenging to acquire a thorough, comprehensive, and understandable reporting of the available data.